Burden, risk factors, and projections of ischemic heart disease in China (1990–2021): findings from the 2021 GBD study - Xu, Sikai; Liu, Zhiyang; Tang, Mu; Xu, Chunli (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIschemic heart disease (IHD) remains a major public health challenge in China. This study aimed to comprehensively analyze the burden of IHD, its risk factors, and future trends from 1990 to 2021 using the Global Burden of Disease database.MethodsWe assessed IHD trends in incidence, prevalence, mortality, and disability-adjusted life years (DALYs) stratified by age (greater than 15 years) and gender. Age-standardized rates, average annual percentage changes, and joinpoint regression analyses were used to evaluate temporal trends. Decomposition and frontier analyses were conducted to identify key contributors to the IHD burden, while future projections were generated for the next 15 years.ResultsIn 2021, the number of IHD incident cases, prevalent cases, deaths, and DALYs in China were 3.17, 3.25, 3.57, and 2.62 times higher than those in 1990, respectively. Age-standardized mortality rates and age-standardized DALYs rates demonstrated an initial increase, followed by a gradual decline. Males showed higher IHD burden during middle age, while elderly females surpassed males in the later years. Aging, high systolic blood pressure, ambient particulate matter pollution, elevated low-density lipoprotein cholesterol, and smoking were the primary drivers of IHD burden. Future projections suggest a declining incidence and prevalence among males but increasing trends in females, with DALYs expected to rise significantly in the female population.ConclusionsThe burden of IHD in China has evolved significantly over the past three decades, driven by demographic and environmental factors. While prevalence and incidence have risen, mortality and DALYs have shown a recent decline, reflecting shifts in disease patterns. Age and gender disparities are evident, with middle-aged males and elderly females disproportionately affected. Key contributors, such as high blood pressure and pollution, highlight the need for targeted interventions. Gender-specific public health strategies, alongside improved environmental and health policies, are essential to mitigating the future burden of IHD in China.